Modified Supporting Materials to Fabricate Form Stable Phase Change Material with High Thermal Energy Storage - Chengbin Yu; Youngseok Song (Molecules, 2023)
Thermal energy storage (TES) is vital to the absorption and release of plenty of external heat for various applications. For such storage, phase change material (PCM) has been considered as a sustainable energy material that can be integrated into a power generator. However, pure PCM has a leakage problem during the phase transition process, and we should fabricate a form stable PCM composite using some supporting materials. To prevent the leakage problem during the phase transition process, two different methods, microencapsulation and 3D porous infiltration, were used to fabricate PCM composites in this work. It was found that both microsphere and 3D porous aerogel supported PCM composites maintained their initial solid state without any leakage during the melting process. Compared with the microencapsulated PCM composite, the 3D porous aerogel supported PCM exhibited a relatively high weight fraction of working material due to its high porosity. In addition, the cross-linked graphene aerogel (GCA) could reduce volume shrinkage effectively during the infiltration process, and the GCA supported PCM composite kept a high latent heat (∆H) and form stability.